Ventilatory Efficiency in Children and Adolescents: A Systematic Review - Parazzi P.L.F. (2015)
Copyright © 2015 Paloma Lopes Francisco Parazzi et al.Introduction. The index of ventilatory efficiency (VE/VCO2) obtained by the progressive exercise test has been considered the gold standard in the prognosis of adults with heart failure, but few studies have evaluated this approach in children. Objective. To verify the scientific evidence about the VE/VCO2 in pediatric and adolescents patients. Methods. A systematic literature review was carried out using the key words VE/VCO2, children, and adolescents using the PEDro and PubMed/MedLine databases. Clinical trials published from 1987 to 2014, including children, adolescents, and young adults up to 25 years, addressing the VE/VCO2 index as a method of evaluation, monitoring, and prognosis were considered. Results. Initially, 95 articles were found; 12 were excluded as the title/abstract did not contain the VE/VCO2 index or because they included patients greater than 25 years of age. From the remaining 83, 58 were repeated between the databases. The final sample consisted of 32 studies including healthy children and children with respiratory and other diseases. Conclusion. There are few studies involving cardiorespiratory assessment by ventilatory efficiency. The studies highlight the fact that high VE/VCO2 values are associated with a worse prognosis of patients due to the relationship with the decrease in pulmonary perfusion and cardiac output.